Parameterization and usability of the Nursing Process System (Research, Society and Development, 2022)
The present study aims to describe the parameterization and usability of the Nursing Process System, a web application formulated to record the steps of the Nursing Process, through the standardized nursing languages ​​of NANDA-I, NIC and NOC. The nursing process guides the documentation of professional nursing practice and is organized into five interdependent and recurring stages. A methodological-descriptive study was carried out, with the participation of 10 nurses and 10 students in the last year of the nursing course working at a university hospital, who evaluated the functionality and usability of SISPE. After inserting the fields for data collection, diagnoses, interventions and nursing results into the system, it was possible to verify the registration of the nursing process by SISPE and the link between its stages. The usability of the system obtained an average score on the SUS scale of 77.2, being evaluated as excellent. Conclusions: the parameterization of SISPE allowed the recording of the steps of the nursing process and the usability of the system was evaluated as excellent.